Meta-analysis: the influence of learning styles on critical thinking of science learning - Hayat, Nor; Yuliani, Hadma; Nastiti, Luvia Ranggi (Universitas Muhammadiyah Mataram, 2024)
This study aims to investigate whether learning styles significantly affect the critical thinking ability of science learning students. The method in this study is a second-order integrative meta-analysis using many data sets from the results of previous research obtained from as many as 13 research journal articles with literature search using electronic databases using the keywords